PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SUMBERDAYA AIR PERMUKAAN DI SUB DAS BENGAWAN SOLO KABUPATEN BOYOLALI BAGIAN SELATAN - , DITYA WISHNU ARIFAL ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The risk of drought and flood can be minimized by managing the potential of surface water resources. The management of surface water can be implemented by the community participation. This research is aimed (1) to map the potential areas of surface water resources and disaster-prone areas (drought and flood), (2) to analyze the characteristics and the level of community participation in the management of surface water resources, and (3) to formulate a strategy of community participation of the proper management of surface water resources in accordance with the condition of the research area. This research employed mixed methods. The sampling employed a proportional sampling method. The variables used were age, gender, education, occupation and income, culture, and the frequency of participation which was analyzed into four participation stages (planning, implementation, utilization, and evaluation). The data were collected by structured interviews and questionnaires (quantitative), as well as by surveys and in-depth interviews (qualitative) to obtain information on the community participation in the management of surface water resources. The results of the research are (1) the potential of the surface water resources in the research area are including spring water, spread in 6 districts (Ampel, Boyolali, Mojosongo, Teras, Banyudono, and Sawit). There are 3 major rivers (Gandul River, Cemoro River, Pepe River), Cengklik Reservoir in Ngemplak District, and ponds in Musuk District and Cepogo District. The vulnerability to drought disaster in 2009 is spread across 9 districts (Selo, Cepogo, Ampel, Musuk, Boyolali, Mojosongo, Sambi, Nogosari, Simo). In 2010, it is spread across 8 villages in Musuk District (Sangup, Jemowo, Sumur, Dragan, Karanganyar, Lampar, Pagerjurang, and Keposong). (2) The level of the participation is generally \"high\" with a score of 148,35 with \"functional participation\" type. The level of community participation in the management of surface water resources at each stage of the planning activities is \"fair\", with a score of 34,79, the implementation stage is \"fair\", with a score of 35,66, the utilization stage is \"high\", with a score of 38,71, and the evaluation is \"high\", with a score of 39,19. The participation category is \"fair\" at the planning and implementation stages, which means the community awareness in performing surface water management is quite high (fair) and is applied quite well. The participation category is \"high\" in the utilization and evaluation stages which means that the community awareness in implementing surface water management tends to be high and is applied well. (3) The policy strategies, according to the SWOT analysis in the management of surface water resources, are prioritizing on the optimization program of the Minapolitan tourism potential, the preservation of the culture/local wisdom, the community empowerment in the regional development, and the construction of road access, including water pipe networks and drainage.